Considerations of Judges of the Binjai Religious Court in Determining the Status of the Missing Defendant in Divorce Cases in the Perspective of Progressive Legal Theory - Raja Alamsyah Hasibuan; Ansari Ansari; Jamil Jamil (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study examines the considerations of religious court judges in determining the time limit for assessing the status of the occult defendant in a divorce case. The research problem lies in the differences between the decisions of the judges and the Compilation of Islamic Law and the opinions of the fiqh scholars. This study analyzes the judge's findings and considerations in the divorce case, contesting Decision Number 331/Pdt.G/2022/PA Bji and Decision Number 346/Pdt.G/2022/PA. Bji and a progressive legal review of the judge's considerations. This type of research is qualitative with a normative approach. The results of the study found that the judge's decision in determining the status of the defendant unseen in the divorce case sued Decision Number 331/Pdt.G/2022/PA Bji was with a span of 10 (ten) months, and 5 (five) years in Decision Number 346/Pdt. G/2022/PA. Bji. These two decisions are based on the consideration of a statement from the village head that the whereabouts of the defendant are unknown (unseen). The judge's review in determining the defendant's status unseen in the divorce case is based on civil law in general. If the defendant has been summoned repeatedly but does not comply with the summons, the judge can decide with a verstek decision. This judge's consideration is a progressive legal finding because the judge finds aspects of the benefit of women in particular and the family (household) in general